Studies on Spectral Properties of Cu(II), Ni(II) and Cu(II) Complexes with Bis-Acenaphthenequinonedioxaime - Rai, H.C.; Rai, B.K. (Asian Journal of Chemistry, 2010)
A series of complexes of the type [M(HL)2] [M = Co(II), Ni(II) and Cu(II) have been prepared by treating ethanolic metal salt solution with the solution of acenaphthenequinonedioxime in tetrahydrofuran. When solutions of these complexes were treated with ammonia or pyridine, another series of complexes of the type [M(HL)2X2] were obtained. The complexes were characterised by elemental analysis, molar conductivity, electronic absorption spectra and infrared spectra. On the basis of experimental data former series was found to be square planar in geometry whereas the latter one to be octahedral.